P-268 Can AI be used as a tool in the evaluation of the risk of pregnancy loss after euploid single embryo transfer?. (30th June 2022) - Yuksel, B; Ozkara, G; Yelke, H; Okten, B; Brualla Mora, A; Derrick, R; Erlich, I; Ozer, G; Kumtepe, Y; Aygun, M; Kahraman, S
Abstract: Study question: Can AI be used as a tool in the evaluation of the risk of pregnancy loss after euploid embryo transfer? Summary answer: AI-annotated tSB (time to start blastulation) and tB (time to formation of full blastocyst) were predictive of miscarriage and live birth. What is known already: Despite the advantage of PGT-A in preventing miscarriages, a pregnancy loss still can occur after the transfer of a chromosomally normal embryo. Unfortunately in the literature there are no clear criteria indicating which morphologically good euploid embryos may be at risk of resulting in pregnancy loss. Study design, size, duration: Retrospective cohort analysis of 455 euploid embryos allowing for the analysis of a range of variables for prediction of live birth or miscarriage from ICSI cycles, that were cultured in the Embryoscope (Vitrolife) at a single clinic (Istanbul Memorial Hospital, ART and Reproductive Genetics Center), and transferred between 2017-2020. This is the largest reported AI study to date predicting outcome in euploid SETs. Participants/materials, setting, methods: Patients were aged between 24-44 years. Each morphokinetic feature was annotated manually and by CHLOE-(Fairtility), and pregnancy outcomes were evaluated. Main results and the role of chance: When annotated using AI, the average time (mean±standard deviation (SD)) for tSB (98±7 vs 97±7, p < 0.05) and tB (106±7 vs 105±, p = 0.02) were significantly longer in patients who miscarried compared to those that did not. Implantation and blastulation scores were not significantly predictive of clinical miscarriage (0.77±0.22 vs 0.74±0.24, NS and 0.97±0.15 vs 0.97±0.16, NS for live birth and miscarriage, respectively). Embryos that aborted and led to live birth had an equal proportion of direct unequal cleavage (DUC) (respectively, DUCs assessed by CHLOE was: 6.8% vs 6.8%, NS). There was no significant difference between the presence of DUC and the pregnancy outcome (miscarriage rate in the presence or absence of DUC was 16.1% vs 16.3%, NS). Limitations, reasons for caution: Retrospective data using embryos selected for transfer Wider implications of the findings: AI-annotated tSB and tB can be added to the already existing range of available evaluation methods for embryo viability and functions which can predict the risk of miscarriage after a euploid embryo transfer. Trial registration number: NA